ILLOCUTIONARY ACTS OF MAIN CHARACTERS IN DEAD POET SOCIETY AND FREEDOM WRITERS - Etika Rachmawati; Adiyatsri Nashrullah; Iskhak Said (Universitas Galuh, 2017)
Abstract: This study analyzed speech acts contextualized in Dead Poet Society and Freedom Writers. This study focused on the use of illocutionary acts used by main characters in both movies. In analyzing the data, this study included content analysis. In this regard, three research questions are addressed: 1) What dominant types and functions of illocutionary acts are uttered by the main characters in certain contextual scenes in both movies? 2) What are the intended meanings of those illocutionary acts?, and 3) How frequently are the illocutionary acts used in both movies? The collected data included 97 utterances of the main character in the Dead Poet Society and 84 utterances in the Freedom Writers which contain illocutionary acts in certain scene contexts. The findings revealed that the kinds of illocutionary acts on both films consisted of five kinds: assertive (representative), directive, commissive, expressive, and declarative. Moreover, the second result of the study showed that the most frequently illocutionary acts used by the main characters in both movies were suitable with its movie scene contexts. Thus, the intended meaning of the main characters are well described and understandable by the viewers. The third result showed the different percentage of the use of illocutionary acts classification expressed by the main characters in both movies. The most frequently used illocutionary in Dead Poet Society is representative (47.06%) which emphasized on informing (30.59%), and directive (45.87%) in Freedom Writers which emphasized on asking (21.10%). Pedagogically, the findings above recommend that the lecturers develop their creativity in teaching pragmatics (sociolinguistics) to improve teaching and learning process by adapting other relevant sources such as movies. Key words: Illocutionary acts, Main Character, Movie